Effective elastic properties variability for two-layered plates of hexagonal and cubic crystals under longitudinal tension. (15th October 2021) - Volkov, Mikhail A.; Demin, Aleksandr I.; Gorodtsov, Valentin A.; Lisovenko, Dmitry S.
Abstract: The problem of longitudinal tension for a two-layered plate of hexagonal and cubic crystals with different orientations of crystallophysic coordinate systems is discussed. Analytical dependencies of effective Young's modulus and Poisson's ratios on thicknesses ratio are obtained. Variability of effective properties is analyzed for all possible combinations of hexagonal and cubic crystals. Significant difference between effective Young's modulus and predictions by rule of mixtures takes place in the case when one of the layers is auxetic. Effective Young's modulus can exceed Young's modulus of the stiffer layer. The ratio of Young's moduli of crystals has significant influence on effective Poisson's ratio. A FEM (finite element method) analysis of this problem was performed and its results were compared with analytical ones. Between the analytical and numerical results qualitative and quantitative correspondence takes place.